EFEKTIFITAS POLISI PAMONG PRAJA SEBAGAI PENYIDIK PEGAWAI NEGERI SIPIL DALAM PENEGAKAN HUKUM PERATURAN DAERAH KABUPATEN PASURUAN NOMOR 2 TAHUN 2017 TENTANG KETERTIBAN UMUM DAN KETENTRAMAN MASYARAKAT - Widada, Gumirlang Kelvin Reymonda (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to find out To analyze and find out about the implementation of law enforcement of Pasuruan Regency Regional Regulation Number 2 of 2017 concerning Public Order and Public Peace. This research was conducted at the Satpol PP office in Pasuruhan Regency. The type of data used was primary data. The data analysis technique was qualitative. The population of this study were Satpol PP employees in Pasuruhan Regency. Using descriptive analysis methods. The results of the implementation of the law enforcement of Pasuruan Regency Regional Regulation Number 2 of 2017 concerning Public Order and Public Peace, the reality in the field of enforcing the Tibum Regional Regulation is very intersecting with the interests of the community at large, in this case the lower middle class community. Furthermore, the synergy between other agencies and law enforcers in implementing the Tibum Regional Regulation was not optimal, so that the Satpol PP of Pasuruan Regency exercised its authority as Satpol PP. Obstacles and solutions in enforcing the Tibum Regional Regulation in Pasuruan Regency, the Satpol PP of Pasuruan Regency is experiencing difficulties due to the absence of reports and evaluations from each Regional Apparatus Organization